Amaranth protein films prepared with high-pressure treated proteins - Condés, María Cristina (2015)
This work studies the effect of using high-pressure modified amaranth proteins in the preparation of edible film and compares the efficiency of high pressure and thermal treatment on the functionality of amaranth protein films. This films were prepared by casting using glycerol as plasticizer from protein dispersions submitted to high pressure treatments of different intensity (0.1, 200, 400 and 600 MPa). Protein dispersions treated with high-pressure were able to form uniform films with better mechanical properties, lower water solubility and water vapor permeability than those prepared from non-treated protein dispersions without modifying its thickness, color and water content, but somewhat more opaque. This could be attributed to structural changes by high-pressure treatment, which favored protein unfolding, increasing protein surface hydrophobicity and the amount of free SH, that were re-associated during film formation producing a higher crosslinking of matrixes that was denoted in a better functionality of films. These films also showed better properties than those prepared with amaranth protein isolates thermally treated.